A Study on the Creation of Sense of Place in the Religious Commercial Ampel Corridors - Astrid Kusumowidagdo; Dyah Kusuma Wardhani; Melania Rahadiyanti (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2024)
The uniqueness of each place needs to be preserved; therefore, this research will explore determining the relationship between the physical and social aspects that create the sense of place. The focus was on two corridors functioning as the primary access to the Grand Mosque of Kampong Ampel and the nodes of the religious and commercial area of Surabaya City, Indonesia. One hundred visitors in each corridor, 200 respondents in total, were surveyed, and data were collected using questionnaires, documentation processes, and interviews with local visitors and pilgrims and analyzed with the multiple linear regression method. The independent variables used were physical and social aspects, while the dependent variable was the sense of place. The results showed that, on average, both physical and social aspects contributed almost the same values to the sense of place in the researched areas. The aspects of the first corridor at the Grand Mosque were found to provide a medium relationship estimated to be 55.0%. In contrast, the second corridor at the Ampel Suci had a higher result, approximately 58.6%, with the social aspect discovered to be higher than the physical aspects of the sense of place. The summary shows that the two corridors have an averagely influence the concept of a sense of place. Based on the finding in this study, it is recommended that both corridors preserve the physical and social aspects of the sense of place, while others should be improved.